2020
DOI: 10.1038/s41385-020-0290-x
|View full text |Cite
|
Sign up to set email alerts
|

Single cell and tissue-transcriptomic analysis of murine bladders reveals age- and TNFα-dependent but microbiota-independent tertiary lymphoid tissue formation

Abstract: Aging has multifaceted effects on the immune system, but how aging affects tissue-specific immunity is not well-defined. Bladder diseases characterized by chronic inflammation are highly prevalent in older women, but mechanisms by which aging promotes these pathologies remain unknown. Tissue transcriptomics of unperturbed, young and aged bladders identified a highly altered immune landscape as a fundamental feature of the aging female bladder. Detailed mapping of immune cells using single cell RNA-sequencing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 64 publications
6
48
0
Order By: Relevance
“…Additionally, large groups of contiguous spots positive for the plasma cell marker Jchain were identified in ST data. Specifically these large clusters of contiguous spots were present in aged but not mature sections (contiguous spots Aged=462, Young=3, Fig.S6) which is in line with a recent report 49 wherein tertiary lymphoid structures, which are highly populated with plasma cells, were more prevalent in aged bladder sections.…”
Section: Resultssupporting
confidence: 91%
“…Additionally, large groups of contiguous spots positive for the plasma cell marker Jchain were identified in ST data. Specifically these large clusters of contiguous spots were present in aged but not mature sections (contiguous spots Aged=462, Young=3, Fig.S6) which is in line with a recent report 49 wherein tertiary lymphoid structures, which are highly populated with plasma cells, were more prevalent in aged bladder sections.…”
Section: Resultssupporting
confidence: 91%
“…While this confirmed the unique bladder transcriptome profiles of the groups under study, many of the top upregulated genes revealed shifts in immune-associated genes with increasing age, suggesting that fundamental changes in the aged murine bladder tissue microenvironment were immune-related. These findings are in concordance with the previous report by Ligon et al, 16 where such changes were reported in female mice.…”
Section: Discussionsupporting
confidence: 94%
“…Such induced TLSs generally provide heterologous humoral immune protection at mucosal sites. 25 As widely reported, TLSs in the bladder also form during the course of normal aging due to increased systemic levels of TNF-α 16 , chronic inflammatory conditions of the urogenital tract such as those observed in interstitial cystitis associated Hunner lesions and bladder cancer. 26-29…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The cause and pathogenic factors of female chronic posterior lesions are not yet completely known. It has been suggested that many factors, including non-specific infection, urethral obstruction, urethral-hymenal fusion, senile atrophy, traumatic causes, inflamm-ageing, and estrogen deficiency, may be implicated in its pathogenesis (4,12,17,18). Urethritis is classified as gonococcal or nongonococcal urethritis (NGU) based on its causative organisms that may be sexually and non-sexually transmitted.…”
Section: Discussionmentioning
confidence: 99%